2015
DOI: 10.4269/ajtmh.14-0425
|View full text |Cite
|
Sign up to set email alerts
|

Mother-to-Child Transmission of Chagas Disease in El Salvador

Abstract: Abstract. To estimate the incidence (any mother to child) and rate (from seropositive mother to child) of motherto-child transmission of Trypanosoma cruzi, a serological census was conducted, targeting pregnant women and infants born to seropositive mothers, in four municipalities of El Salvador. Of 943 pregnant women, 36 (3.8%) were seropositive for T. cruzi. Of 36, 32 proceeded to serological tests of their infants when they became 6-8 months of age. Six infants seropositive at the age of 6-8 months further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…[6][7][8] A recent study identified one case of congenital Chagas disease among 32 infected mothers in El Salvador. 9 It has been suggested that the congenital transmission rate might vary according to the parasite's genotype, but available data are inconclusive. [10][11][12][13] Trypanosoma cruzi genotypes have been grouped into discrete typing units (DTUs), with TcI being assumed to be more frequent in Mexico and Central America and non-TcI (TcII-VI) being dominant in the Southern Cone region of South America.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] A recent study identified one case of congenital Chagas disease among 32 infected mothers in El Salvador. 9 It has been suggested that the congenital transmission rate might vary according to the parasite's genotype, but available data are inconclusive. [10][11][12][13] Trypanosoma cruzi genotypes have been grouped into discrete typing units (DTUs), with TcI being assumed to be more frequent in Mexico and Central America and non-TcI (TcII-VI) being dominant in the Southern Cone region of South America.…”
Section: Introductionmentioning
confidence: 99%
“…This serosurvey identified 2.3% of children were reactive on two different antibody assays. The last surveillance efforts were performed in 2008–2011: 1% prevalence in children <16 years [ 31 ], 4% prevalence among pregnant mothers with a 3% congenital transmission rate [ 11 ], and a total of 731 acute cases continually reported from 2000–2012 [ 10 ]. In comparison, an El Salvadorian blood bank surveillance study of adults found a continual decline in annual positivity from 3.7% to 1.7% during 2001–2011 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transmission source of these chronic pediatric Chagas disease cases is believed to be vectorial; however, the potential for mother-to-child transmission cannot be ruled out. This study was unable to serologically test mothers for Chagas disease, and the latest estimates suggest approximately 3% of infected mothers will congenitally transmit infection to their infants [ 11 ]. This study was also unable to establish seasonality related to vector activity since seroprevalence does not indicate acute infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations